The evolution of heat exposure in changing societies and a changing climate from 1960 to 2100 - Schäfer, Andreas M.; Ludwig, Patrick; Krikau, Svea; Benz, Susanne A.; Mühr, Bernhard; Mohr, Susanna; Kunz, Michael (Frontiers in Climate, 2025)
With climate change, human exposure to heat has increased over recent decades and is expected to substantially increase in the future. This study introduces a novel metric – namely, the exponentially weighted degree-day approach – to assess population-weighted heat exposure at the national level, incorporating both static and dynamic population scenarios. Using ERA5 reanalysis and CMIP6 climate projections under the SSP2-4.5 and SSP5-8.5 scenarios, we analyze and categorize global heat exposure and its trends from 1960 until 2100. Our findings reveal a significant rise in heat exposure over past decades, disentangling the contributions of climate and demographic changes. Furthermore, a thorough analysis of biases across different datasets and model dimensions provides a global perspective based on daily maximum and daily mean temperatures. This analysis forms the basis for quantifying current and future heat exposure, together with a qualitative heat zone classification scheme. The results underscore the urgent need for targeted adaptation strategies and improved climate metrics to better assess and mitigate future heat-related risks.